The Effect of Liquidity and Sales Growth on Tax Avoidance in Various Consumer Goods Industry Sector Companies Listed on the Indonesia Stock Exchange for the 2014-2018 Period - Mervin Nyoriman (Outline Publisher, 2022)
This study aims to determine the significant effect of Liquidity and Sales Growth on Tax Avoidance in various consumer goods industry companies listed on the Indonesia Stock Exchange Period 2014-2018. The population in this study is the Various Consumer Goods Industry companies on the Indonesia Stock Exchange in the 2014-2018 period as many as 46 companies. The research sample in this study were 11 companies with a purposive sampling technique. Data analysis techniques using multiple linear regression analysis methods. T test results show that liquidity has no effect on Tax Avoidance in various consumer goods industry companies Listed on the Indonesia Stock Exchange Period 2014-2018 and Sales Growth has a significant effect on Tax Avoidance in various consumer goods industry companies Listed on the Indonesia Stock Exchange Period 2014-2018. F test results show that the Liquidity and Sales Growth variables significantly influence the Tax Avoidance at various consumer goods industry companies Listed on the Indonesia Stock Exchange Period 2014-2018. The coefficient of determination test results (R2) shows that the Tax Avoidance variable can still be explained by the Liquidity and Sales Growth variables while the remaining Tax Avoidance variables can be explained by other variables not examined in this study such as Leverage and Profitability.